Mu rhythm desynchronization reveals motoric influences of hand action on object recognition - Kumar, Sanjay; Riddoch, Margaret J.; Humphreys, Glyn (Frontiers in Human Neuroscience, 2013)
We examined the effect of hand grip on object recognition by studying the modulation of the mu rhythm when participants made object decisions to objects and non-objects shown with congruent or incongruent hand-grip actions. Despite the grip responses being irrelevant to the task, mu rhythm activity on the scalp over motor and pre-motor cortex was sensitive to the congruency of the hand grip—in particular the event-related desynchronization of the mu rhythm was more pronounced for familiar objects grasped with an appropriate grip than for objects given an inappropriate grasp. Also the power of mu activity correlated with RTs to congruently gripped objects. The results suggest that familiar motor responses evoked by the appropriateness of a hand grip facilitate recognition responses to objects.